Effects of concentrate feeding sequence on VFA production, and cecal microbiota of Dezhou donkeys by metagenomic technology - Cai, Changyun; Xie, Lan; Xing, Jingya; Lu, Ting; Qi, Xingzhen; Li, Lanjie; Chen, Xue; Akhtar, Muhammad Faheem; Jin, Yaqian; Liu, Guiqin (Frontiers in Veterinary Science, 2024)
Microorganisms residing in the cecum of donkeys are crucial for physiological processes, nutrient metabolism, and immune function. Fifteen Dezhou donkeys with similar age and weight profiles were randomly divided into three groups with the concentrate feeding sequence: fiber-to-concentrate (FC), concentrate-to-fiber (CF), and total mixed ration (TMR). The experiment spanned a duration of 82 days. Employing high-throughput sequencing technology, we assessed nutrient digestibility and subsequently characterized the composition and functional capacity of the cecal microbiota across different feeding sequences. The experimental findings revealed that the levels of valeric acid were notably higher in the CF and TMR groups compared to the FC group (P<0.05). However, no significant differences were observed between the CF and TMR groups (P>0.05). These results suggest that the feeding sequence exerts a certain impact on the microbial composition within the cecum of Dezhou donkeys. At the phylum level, the predominant microbiota consisted of Firmicutes and Bacteroidetes, with the CF group displaying a higher relative abundance of Firmicutes compared to both the FC and TMR groups. At the genus level, Prevotella, Bacteroides, and Fibrobacter were the dominant bacterial genera identified in cecum. The functional gene annotation analysis indicated a significantly lower abundance of lacZ (K01190), Por/nifJ (K03737), and ppdK (K01006) genes in CF group relative to the FC and TMR groups (P<0.05), highlighting their roles in galactose metabolism and glycolysis, respectively. Moreover, the CF group exhibited a higher concentration of antibiotic resistance genes (tetO and tet44) in the gut microbiota compared to the TMR and FC groups (P<0.05), underscoring the presence of numerous antibiotic resistance genes within the phyla Bacteroidetes, Firmicutes, and Proteobacteria. In conclusion, different precision feed sequences significantly impact the levels of volatile fatty acids in Dezhou fattening donkeys, modify the composition and functional genes of the cecal microbiota, and elucidate the microbial mechanisms influenced by the feeding sequence on the growth and metabolism. These insights are anticipated to provide a foundation for the rational design of precision feed sequences in practical agricultural settings.